2015
DOI: 10.5535/arm.2015.39.6.941
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Adhesiolysis Versus Transforaminal Epidural Steroid Injection for the Treatment of Chronic Radicular Pain Caused by Lumbar Foraminal Spinal Stenosis: A Retrospective Comparative Study

Abstract: ObjectiveTo investigate the efficacy of percutaneous adhesiolysis (PA) compared to fluoroscopy (FL)-guided transforaminal epidural steroid injection (TFESI) in patients with radicular pain caused by lumbar foraminal spinal stenosis (LFSS) by assessing pain relief and functional improvement at 4 and 12 weeks post-procedure.MethodsThis retrospective study included 45 patients who underwent PA or FL-guided TFSEI for radicular pain caused by LFSS of at least 3 months' duration. Outcomes were assessed with the Oswe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In [28], the degree of the lateral canal stenosis in the MRI did not correlate with the initial TFESI-induced pain relief of the patients with the degenerative lumbar scoliosis stenosis. Likewise, a number of articles discuss the effectiveness of TFESIs in patients with spinal stenosis [29303132]; according to these articles, there is a dearth of evidence regarding the effectiveness of TFESIs for the radicular pain that is caused by the spinal stenosis. In addition, in a previous study, the severity of the spinal stenosis is not significantly different for the patients with the improvement compared with the patients without the improvement [33].…”
Section: Discussionmentioning
confidence: 99%
“…In [28], the degree of the lateral canal stenosis in the MRI did not correlate with the initial TFESI-induced pain relief of the patients with the degenerative lumbar scoliosis stenosis. Likewise, a number of articles discuss the effectiveness of TFESIs in patients with spinal stenosis [29303132]; according to these articles, there is a dearth of evidence regarding the effectiveness of TFESIs for the radicular pain that is caused by the spinal stenosis. In addition, in a previous study, the severity of the spinal stenosis is not significantly different for the patients with the improvement compared with the patients without the improvement [33].…”
Section: Discussionmentioning
confidence: 99%
“…For the management of radicular pain, various conservative treatments have been applied for patients with LFSS. Transforaminal epidural steroid injection (TFESI) is one of the most effective methods for controlling radicular pain after LFSS and has been increasingly used lately (6)(7)(8)(9)(10)(11)(12). Corticosteroids inhibit the synthesis of various pro-inflammatory mediators (13).…”
Section: Tfesi Proceduresmentioning
confidence: 99%
“…Therefore, TFESI can reduce nerve root inflammation induced by mechanical compression at the narrowed foramen. Several previous studies demonstrated the effectiveness of TFESI on reducing radicular pain after LFSS (6)(7)(8)(9)(10)(11)(12). However, little is known about the treatment outcome of TFESI according to the severity of LFSS.…”
Section: Tfesi Proceduresmentioning
confidence: 99%
“…The short‐term positive effectiveness of TFESI for controlling radicular pain following LSS has been well demonstrated in several previous studies 7,11–14 . However, the long‐term outcome of TFESI on LSS has been rarely studied.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, it can block the transmission of nociceptive signals through the nerve fibers 10 . The short‐term pain‐reducing effects of lumbar TFESI is well demonstrated 7,11–14 . However, little is known about the long‐term effect of lumbar TFESI for managing lumbar radicular pain due to LSS.…”
Section: Introductionmentioning
confidence: 99%